Pengaruh Perkembangan Kerupuk Emping Diera Digital Terhadap Kepuasan Pelanggan Di Kota Cirebon - Yahya, Irfan; Pranata, Sudadi; Fauzi, Feri (Awatara Publisher, 2025)
This study aims to analyze the effect of the development of digitalized emping (traditional crackers) on customer satisfaction in Cirebon City. The background of this research lies in the growing digitalization of SMEs, including traditional food products like emping. This study employs a quantitative approach using a simple linear regression method. The sample consisted of 100 respondents who are online customers of emping. The results show that the digital development of emping has a positive and significant effect on customer satisfaction, with a coefficient value of 0.490 and a significance level of 0.000. This indicates that the better the digital transformation implemented by emping producers, the higher the customer satisfaction. The findings support Oliver’s (1997) customer satisfaction theory, emphasizing the match between expectations and perceptions of service performance. This study offers practical implications for SMEs to improve their digital strategies to retain customer loyalty and provides academic contributions to extending customer satisfaction theory in the context of traditional local products.